The Predictive Value of 3D Time-of-Flight MR Angiography in Assessment of Brain Arteriovenous Malformation Obliteration after Radiosurgery - Buis, D.R. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: The purpose of radiosurgery of bAVMs is complete angiographic obliteration of its nidus. We assessed the diagnostic accuracy of 1.5T T2-weighted MR imaging and TOF-MRA images for detecting nidus obliteration after radiosurgery. MATERIALS AND METHODS: The pre- and postradiosurgery MR images and DSA images from 120 patients who were radiosurgically treated for a bAVM were re-evaluated by 2 observers for patency of the nidus (preradiosurgery) and obliteration (postradiosurgery: final follow-up MR imaging), by using a 3-point scale of confidence. Consensus reading of the DSA after radiosurgery was considered the criterion standard for obliteration. Sensitivity, specificity, PPVs, and NPVs, and overall diagnostic performance by using ROC were determined. RESULTS: Mean bAVM volume during radiosurgery was 3.4 mL (95% CI, 2.6–4.3 mL). Sixty-six patients (55%) had undergone previous endovascular embolization. The mean intervals between radiosurgery and follow-up MR imaging and for DSA, respectively, were 35.6 months (95% CI, 32.3–38.9 months) and 42.1 months (95% CI, 40.3–44.0 months). With ROC, an area under curve of 0.81–0.83 was found. PPVs and NPVs of final follow-up MR imaging for definitive obliteration varied between 0.85 and 0.95 and 0.55 and 0.62. An average false-positive rate, meaning overestimation of nidus obliteration, of 0.08 and an average false-negative rate, meaning underestimation of nidus obliteration of 0.48, were found. CONCLUSIONS: MRA is insufficient to diagnose obliteration in the follow-up of bAVMs after radiosurgery. A remaining nidus diameter <10 mm seems to be the major limiting factor for reliable assessment of obliteration. We highly recommend follow-up DSA for definitive diagnosis of complete obliteration.